(3fXe bhGYO GdEYQGHs - (3YHO GdSdGe Hf GdWjH Hf eMeO GdbGOQj GdMSfj GdeZQHj GdaGSj, CHh eMeO,J (B1110 (3g` s; (3YHO Gddg Hf jhSa Hf CMeO Hf YHO Gddg Hf jhSa, CHh eMeO, LeGd GdOjf, GHf gTGe ,J (B761 (3g` s
(3ChdgG (B:s
(3jbhd GdMeO ddg GdPj bO CLed dfG ef GdNjQ GdLRjd oLedG hgPg CQLhRI efXheI bhGYO GdEYQGH ajgG eMceI s
(3BNQgG (B:s
(3Gddg jfaY Hg ceG faY HCUdg dcd ef dg JHY GfJgJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B127 - (3U(B151s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B331 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs